Deceleration capacity of heart rate predicts 1‐year mortality of patients undergoing transcatheter aortic valve implantation. Issue 10 (28th August 2017) - Duckheim, Martin; Bensch, Charlotte; Kittlitz, Linn; Götz, Nin; Klee, Katharina; Groga‐Bada, Patrick; Mizera, Lars; Gawaz, Meinrad; Zuern, Christine; Eick, Christian
Abstract : Background: Risk prediction in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI) is challenging. Development of novel markers for patient risk assessment is of great clinical value. Deceleration capacity (DC) of heart rate is a strong risk predictor in post‐infarction patients. Hypothesis: DC provides prognostic information in patients undergoing TAVI. Methods: We enrolled 374 consecutive patients with severe AS undergoing TAVI. All patients received 24‐hour Holter recording or continuous heart‐rate monitoring to assess DC before intervention. Primary endpoint was all‐cause mortality after 1 year. Results: Forty‐nine patients (13.1%) died within 1 year. DC was significantly lower in nonsurvivors than in survivors (1.2 ± 4.8 ms vs 3.3 ± 2.9 ms; P < 0.001), whereas the logistic EuroSCORE and EuroSCORE II were comparable between groups (logistic EuroSCORE: 27.3% ± 17.0% vs 22.9% ± 14.2%; P = 0.122; EuroSCORE II: 8.0% ± 6.9% vs 6.7% ± 4.8%, P = 0.673). One‐year mortality in the 116 patients with impaired DC (<2.5 ms) was significantly higher than in patients with normal DC (23.3% vs 8.5%; P < 0.001). In multivariate Cox regression analysis that included DC, sex, paroxysmal atrial fibrillation, hemoglobin level before TAVI, and logistic EuroSCORE, DC was the strongest predictor of 1‐year mortality (hazard ratio: 0.88, 95% confidence interval: 0.85‐0.94, P < 0.001). DC yielded an AUC in the ROC analysis of 0.645. Conclusions: DC of heart rate is a strong and independent predictor of 1‐year mortality in patients with severe AS undergoing TAVI.